Globalisierung und Terror - Hirsch, Joachim (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
The new form of international terrorism shows complex relations to the capitalist globalization process. It is argued that the present international system – despite of the absolute economic and military dominance of the „strong states” under US-leadership – is marked by a fundamental lack of political hegemony. The crisis of politics resulting from this „non hegemonial” situation is based in a fundamental contradiction of the neoliberal globalization project. The reactions of the dominant states to the terrorist attacks are suited to deepen and to intensify this political crisis.